A dynamic approach for location management in IP-based networks - Hassan, W. H.; Hassan, A.; Fisal, Norshiela (Institute of Electrical and Electronics Engineers, 2008)

(untitled)
An approach is presented to facilitate location management of mobile hosts using a distributed intelligent architecture. Intelligence is imbued onto an IP-based network as an overlay to provide mobility services. The overlay consists of a three-layered multiagent architecture that would provide the necessary signaling and control information to support mobility. Dynamism in the network is accomplished through the use of this ‘agency’. This represents a departure from traditional methods of providing mobility services to hosts